PERBEDAAN DAYA TAHAN JANTUNG PARU ANTARA SISWA ORANGTUANYA PEGAWAI NEGERI DENGAN PETANI/NELAYAN - Budiman Budiman (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
Students who attend BIna Generasi Bangsa Junior High School come from different parental backgrounds, both from civil servants and farmers and even fishermen. The hypothesis is